Modelling and experimental contrast of the mechanical behaviour of structural laminated glass - Sanz-Ablanedo, E.; Lamela, M. J.; Rodríguez-Pérez, José R.; Arias, P. (Materiales de Construcción, 2010)
This paper presents a numerical simulation of the mechanical behaviour of laminated glass plates (glass- PVB-glass) and its experimental verification. The viscoelastic characterization of the intermediate layer of PVB has been done by means of stress relaxation tests at various temperatures. The consideration of PVB as a viscoelastic material permits to analyze the real response of the structural element of laminated glass under time variations of temperature, of application of loading, of stress state, etc. Displacements obtained with the numerical analysis have been verified experimentally with laminated glass plates under lateral load using close range photogrammetry and dial gauges indicators. The analysis of results confirms the time dependent behaviour of the glass-PVB-glass laminate and suggests the validity of the proposed model.